THE INFLUENCES OF PRODUCT, PRICE, PROMOTION, PLACE, AND SERVICE QUALITY TOWARDS CUSTOMER SATISFACTION - Muhamad Banu Kamal Alfirdaus; Utami Tri Sulistyorini (Nurul Jadid University, 2025)
This study aims to analyze the influence of product, price, promotion, location, and service quality on customer satisfaction at PT. Bank Muamalat Indonesia Semarang Branch Office, both simultaneously and partially. The data used are primary data collected using a questionnaire. The population in this study were all savings customers at PT. Bank Muamalat Indonesia Semarang Branch Office. With the purposive sampling method, 100 samples were obtained that were suitable for study. The analysis model in this study used a multiple linear regression analysis model and the analysis technique used the F Test, the Coefficient of Determination Test (R2), and the t Test processed using the SPSS 22.0 program. The results of this study indicate that the variables of product, price, promotion, location, and service quality simultaneously have a significant effect on customer satisfaction. Furthermore, product, price, promotion, location, and service quality each partially have a positive and significant effect on customer satisfaction at PT. Bank Muamalat Indonesia Semarang Branch Office